Measurement of somatosensory evoked magnetic fields using an adjustable magnetoresistive sensor array - Tatsuoka, Tetsuro; Kawabata, Shigenori; Hashimoto, Jun; Hoshino, Yuko; Sekihara, Kensuke; Shibuya, Tomohiko; Adachi, Yoshiaki; Okawa, Atsushi (Sensors and actuators. A. Physical., 2024)
An adjustable helmet-style magnetoresistive (MR) sensor array with room-temperature magnetic flux sensors was developed to demonstrate the simultaneous multipoint measurement of the somatosensory evoked magnetic field (SEF). Utilizing the extended sensor length, we designed the array to permit individual radial adjustment of each sensor, thereby achieving a precise fit to the varied head geometries of different subjects. Furthermore, the geometry of the sensor array precisely adjusted for the individual subject was quickly obtained by calibration. The SEF was measured in three healthy subjects using an array of 30-channel MR sensors placed on the left hemisphere of the head with median nerve stimulation in the right wrist and averaged over 8000 measurements. An M20 component considered to originate from the primary somatosensory cortex was observed at an approximate latency of 20 ms of the magnetic field waveform in all cases (maximum amplitude of 725 ± 257 fT, peak latency of 20.5 ± 0.45 ms). The phase inversion observed around C3 in the international 10–20 system corresponded to the palmar area of the primary somatosensory cortex on the contour map of the magnetic field at the M20 peak. The MR sensor, an affordable and easy-to-use magnetic sensor that does not require a zero-field environment nor a cryogenic apparatus, was successfully used for simultaneous multipoint SEF measurements in humans and provides a promising system for realizing magnetoencephalography application devices. [Display omitted] •Adjustable helmet-style MR sensor array developed.•Sensor positions on the array can be individually adjusted in the radial direction.•The MR sensor does not require a zero-field environment or cryogenic apparatus.•Simultaneous multipoint SEF measurement demonstrated using the developed sensor.